(untitled) (The Strategic Review for Southern Africa, 2020)
This article analyses relations between South Africa's national and provincial governments on foreign affairs over the past 20 years. It departs from the premise that the idea of relative autonomy ofsubnational governments, which is embedded in South Africa's 1996 constitution, has remained largely underdeveloped owing to factors such as inherent ambiguities in the constitutional design, a strong centralising ethos on the part of the ruling party and generally weak provincial capacities. Consequently, relations between the national and provincial governments on foreign affairs have been low-key, predominantly focused on technical matters and generally of a top-down nature. Provincial governments have been virtually absent from the foreign policy-making process despite constitutional provisions to that effect. What is more, the article notes that intergovernmental processes intended to coordinate provincial international relations and align them with national development priorities and South Africa's foreign policy have for the most part been ineffective and inefficient.